2012
DOI: 10.1177/0890334412451364
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Swallows as a Measure of Breast Milk Intake in the First Days of Life

Abstract: Pre-and postfeed weights have been established as the best way to determine adequacy of breast milk intake. However, assessments such as listening for swallows are done to evaluate breastfeeding. Newly Expressed This study indicates that, in the first few days of life, audible swallows are not a reliable or valid measure of breast milk intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In a study investigating the reliability and validity of swallows to measure of breast milk intake in the first days of life, 30 healthy term infants were evaluated during feeding . Audible swallow number was counted and confirmed on the videotape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating the reliability and validity of swallows to measure of breast milk intake in the first days of life, 30 healthy term infants were evaluated during feeding . Audible swallow number was counted and confirmed on the videotape.…”
Section: Discussionmentioning
confidence: 99%
“…In Côté‐Arsenault et al. 's study, only healthy term infants were evaluated and two lactation consultant assessed swallow counts, but there were clinically important discrepancies. One of the limitation of that study was evaluation of the recordings was not well due to infant position and sound quality.…”
Section: Discussionmentioning
confidence: 99%
“…While intra-oral vacuum is important to milk removal, excessive intra-oral vacuum has been associated with nipple pain. More than 60 years ago Gunther reported a sucking intra-oral vacuum up to −200 mmHg in a 2 day-old infant that was associated with nipple pain and damage [ 144 ]. Recently, McClellan et al [ 145 ] reported that infants of mothers with persistent nipple pain exerted stronger mean baseline (pain: −91 mmHg; no pain −51 mmHg) and peak intra-oral vacuums (pain: −214 mmHg; no pain: −153 mmHg).…”
Section: Nipple Painmentioning
confidence: 99%
“…Audible swallowing was considered as a valid observational indicator to determine milk intake per individual feed [6] [7] [9] . However, there was great variation among observers, and observers should be trained to recognize feeding patterns [7] .…”
Section: Introductionmentioning
confidence: 99%